Մայրական սիրո և պանդխտության թեման Ավետիք Իսահակյանի պոեզիայում - Իսահակյան, Բելլա (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
В поэзии Исаакяна тема материнской любви занимает одно из центральных мест. Образу матери посвящено множество лирических стихотворений поэта: «Моей матери» (пер. А. Блока), «Что над огнем ты варишь, мать?» (пер. А. Блока), «Колыбельная» (пер. А. Блока), «Караван мой бренчит и смеется» (пер. А. Блока), «Мне грезится: вечер мирен и ти х ...» (пер. А. Блока), «Сон» (пер. А. Яшина), «Мне сказали: «Давно умерла твоя мать...» (пер. А. Ахматовой). Помимо стихов, образу матери А. Исаакяном посвящены великолепные строки в поэме «Абул Ала Маари» (пер. В. Брюсова), а также в легендах и балладах: «Скиталец сын» (пер. В. Иванова), «Сердце матери» (армянское предание), «Мать» (Ширакское предание), «Сыновняя любовь», в рассказе «Непобедимый дух», а также в стихах более позднего периода: «Мать увидела меня - очень грустным...», «Смотри мама - как солнце...», «Печаль со мной, и со мной идет...». Другой ключевой темой его поэзии была тема скитальчества - любви и тоски по далекой родине. Образ матери - Алмаст - часто олицетворяет образ родины поэта - Армению, а скиталец является олицетворением образа армянина - борца за освобождение родного народа от турецкого гнета. Մայրական սիրո և պանդխտության թեման... In Isahakyan's poetry, the theme of maternal love occupies one of the central places. Many lyrical poems of the poet are devoted to the image of the mother: “My Mother” (trans. A. Blok), “What are You Cooking over Fire, Mother?” (A. Blok lane), “ Lullaby” (trans. A. Blok), “My Caravan is Jingling and Laughing” (trans. A. Blok), I dream: the evening is peaceful and quiet... (trans. A. Blok), “Dream” (trans. A. Yashin), “ I was Told: “Your mother died a long time ago... ” (trans. A. Akhmatova). In addition to poems, the image of A. Isahakyan's mother is portrayed with the magnificent lines in the poem “Abul Ala Maari” (trans. by V. Bryusov), as well as in legends and ballads: “The Wanderer Son” (trans. V. Ivanov), “Mother's Heart” (Armenian tradition), “Mother” (Shirak tradition), “ Filial Love” , in the story “ Invincible Spirit” , as well as in poems of a later period: “Mother Saw Me - Very Sad “ Look at My Mother - like the Sun “Sadness is with Me, and with Me Goes Another key theme of his poetry was the theme of wandering - love and longing for a distant homeland. The image of the mother - Almast - often personifies the image of the poet's homeland - Armenia, while the wanderer is an embodiment of an Armenian, the fighter for the liberation of his native people from the Turkish yoke.
Keywords: Բանասիրություն